Study on regulation of VGSCS expression by REST using AZA in MCF-7 breast cancer cell line - Rason, Nursyuhana (Universiti Sains Malaysia, 2014)
The Repressor Element 1-Silencing Transcription factor (REST) mediates the repression of several neuronal genes in non-neuronal cells. REST represses its target gene through histone deacetylation, chromatin remodeling and methylation. Loss of DNA methylation has been reported as an early event in tumorigenesis and could possibly explained the increased expression of neuronal genes including voltage-gated sodium channels (VGSCs) in cancer cells. The question remain, is REST regulates VGSC expression in breast cancer? In this study, a DNA methylation inhibitor 5-azacytidine (AZA) was used to inhibit REST function and test its effects on proliferation and the expression of REST common target genes and VGSCs in the weakly metastatic breast cancer cells, MCF-7. MTT assay was carried out to determine the effect of AZA treatment on cell growth at different concentration, 100 pM - 1 mM for 24, 48 and 72 h. Total RNA extraction, cDNA synthesis, PCRs, gel electrophoresis and image analysis were conducted to investigate the effects of AZA on the gene expression of synaptophysin (SYP), chromagranin A (CHGA), both REST common target genes and VGSCs (Nav1.5 and nNav1.5). Results showed that AZA caused a dose-dependent decreased on the viability of MCF-7 cells where the effect was prominent at highest concentration, 1 mM after 72 h of treatment. REST common target genes, SYP and CHGA had an increased pattern in expression after AZA treatment. Interestingly, an increased expression pattern of Nav1.5 and nNav1.5 was also observed, though the increments of expression of these genes were not significant. Herein, a possibility that Nav1.5 and nNav1.5 in breast cancer cells are REST target gene could be postulated, though further works are needed to confirm the interaction.